REVIEW ARTIKEL: POTENSI GAMAVUTON-0 SEBAGAI ANTI ARTRITIS REMATOID MELALUI PENGHAMBATAN SITOKIN IL-1Ã - Rosyidi, Viddy Agustian (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2012)
Rheumatoid Arthritis is a chronic and systemic inflammatory disease that can destruct joint tissues. The disease progression is associated with elevated levels of interleukin 1Ã (IL-1Ã) produced by macrophages and dendritic cells. Gamavuton-0 (GVT-0) has been known to have anti-inflammatory effect related to this activity inhibit COX-2, anti-oxidative, and radical scavenger. GVT-0 can modulate the expression of inducible inflammatory cytokines. Administration of GVT-0 significantly suppressed the progression of Rheumatoid Arthritis and inhibited the production of IL-1Î². GVT-0 can be developed as a potential therapy for Rheumatoid Arthritis due to the activity inhibits the production of IL-1Ã.